Διερεύνηση του ρόλου του διευθυντή της σχολικής μονάδας, κατά τον ψηφιακό μετασχηματισμό: Ευθύνες και προκλήσεις. - Αναστασίου, Μιχάλης (Ανοικτή Εκπαίδευση: το περιοδικό για την Ανοικτή και εξ Αποστάσεως Εκπαίδευση και την Εκπαιδευτική Τεχνολογία, 2025)
Extended Summary: The purpose of this qualitative research is to investigate the role and the main challenges faced by the principal during the process of digital transformation in the school unit. For this reason, three research questions have been posed: a) What is the significance of digital transformation for the school unit? b) What is the evolving role of the principal in the digital transformation of the school unit?, and c) What are the major challenges faced by the principal during the digital transformation of the school unit? This research was conducted using a descriptive qualitative case study. To investigate the views of principals, the method of semi-structured interviews was used, which included a set of predetermined questions. The interview questionnaire contained 10 open-ended questions and it was divided into three parts. The first part concerned the process of digital transformation in the school unit. The second part explored the role of the principal, and the third part examined the challenges faced by the principal in the digital transformation. The selection of principals (n = 12) for the research was done using judgmental sampling due to the specific professional characteristics (secondary education principals) of the participants. The results of the research highlighted the strategic and vital importance role of the principal in the digital transformation process and the responsibility of creating a functional ecosystem with the collective and active involvement of all school stakeholders. The principal is responsible for crystallizing the multifaceted, economic, and social developments and digital changes within the strict legal framework of the public school, in an effort to create a proper functional and learning culture in the workplace. However, the lack of necessary digital competence in terms of skills and infrastructure, combined with the complexity of change and the emerging new work and learning realities, emerged as the main deterrent factors. At the same time, the absence of a specialized digital department or expert and the non-mandatory integration of digital skills into the curriculum lead to a significant slowdown not only of the principal's role effectiveness but also of the digital transformation process in the school unit. Περίληψη Ο σκοπός της παρούσας ποιοτικής έρευνας είναι να διερευνήσει το ρόλο και τις κυριότερες δυσκολίες που αντιμετωπίζει ο διευθυντής, κατά τη διαδικασία του ψηφιακού μετασχηματισμού στη σχολική μονάδα. Τα αποτελέσματα της έρευνας ανέδειξαν τον στρατηγικό ρόλο του διευθυντή στη διαδικασία του ψηφιακού μετασχηματισμού και την ευθύνη δημιουργίας ενός λειτουργικού οικοσυστήματος με συλλογική και ενεργό εμπλοκή όλων των σχολικών εταίρων. Ο διευθυντής έχει την ευθύνη να αποκρυσταλλώσει, μέσα στο στενό νομικό πλαίσιο του δημόσιου σχολείου, τις πολυμορφικές, οικονομικές και κοινωνικές εξελίξεις και ψηφιακές αλλαγές στην προσπάθεια του να δημιουργήσει μια σωστή λειτουργική και μαθησιακή κουλτούρα στο χώρο εργασίας. Ωστόσο, η έλλειψη της αναγκαίας ψηφιακής επάρκειας σε επίπεδο δεξιοτήτων και υποδομής, σε συνδυασμό με τη δεινότητα της αλλαγής και των διαμορφούμενων νέων εργασιακών και μαθησιακών πραγματικοτήτων, αναδείχθηκαν ως οι κύριοι αποτρεπτικοί παράγοντες. Ταυτόχρονα, η απουσία ενός εξειδικευμένου ψηφιακού τμήματος ή ειδήμονα και η μη υποχρεωτική ενσωμάτωση των ψηφιακών δεξιοτήτων στο αναλυτικό πρόγραμμα, οδηγούν σε σοβαρή επιβράδυνση όχι μόνο του ρόλου του διευθυντή αλλά και της διαδικασίας του ψηφιακού μετασχηματισμού στη σχολική μονάδα.